Peran Stres Kerja dan Komitmen Organisasional pada Pengaruh Konflik Pekerjaan Terhadap Kinerja Pegawai di PLN Distribusi Jaringan Surabaya Timur - Arif Hartadi; Siti Mujanah; Achmad Yanu Alif Fianto (PKP Fakultas Syariah LPPM IAI Nasional Laa Roiba, 2024)
One thing that can affect employee performance is work stress, which is a condition of tension that affects the emotions, way of thinking and physical condition of employees. This research investigates the influence of job stress and organizational commitment on job conflict. Also investigate whether work conflict makes a good mediator. This study conducted a survey of employees at the PLN East Surabaya Distribution Network. Using the saturated sampling method, on 102 employees. The data was then analyzed using Structural Equation Modeling. The findings show that work stress and organizational commitment make a positive contribution to work conflict. Research also proves that work conflict mediates the relationship between work stress and organizational commitment on employee performance. This study contributes to understanding employee behavior by using a framework of job conflict and employee performance in state companies, which can also be applied to other public companies.